Does water-saving irrigation truly conserve water? Yes and No - Zhao, N.; Zheng, X.; Zhang, B.; Tian, S.; Du, L.; Li, Y. (Elsevier, 2025)
Irrigation is by far the largest consumer of freshwater, and is thus widely acknowledged as a major contributor to water scarcity. Consequently, water-saving technologies (WST) are considered to be effective in reducing irrigation water use and alleviating water scarcity. However, growing evidence indicates that looking at the larger spatial scale, these technologies may exacerbate water scarcity, particularly in arid regions. This study evaluated the water-saving effect at the field and regional scales based on a water accounting framework for an arid oasis region in Northwest China. The results showed that, with the application of WST, irrigation volume decreased by 1012.95 m³/ha over 20 years, with reduced soil evaporation for 80.4 % of the cropland. However, the perceived water saving gives the misleading impression that overall water use is declining, encouraging farmers to expand irrigated areas in pursuit of higher profits. Our results confirmed that the expansion leads to more water consumption at a regional scale. More importantly, this study highlighted that not all water losses are wasteful. Drainage plays a crucial ecological role in salt leaching and nourishing adjacent desert vegetation. Its significant reduction has occurred alongside noticeable drops in groundwater levels in the oasis-desert ecotone, which has subsequently led to vegetation degradation. These findings provide valuable insights for implementing water-saving measures in arid regions worldwide and serve as a warning that the overuse of WST in such areas could exacerbate water scarcity and ecological crises.